The effects of city and municipality characteristics on an individual's likelihood to use electronic payments - Tannagan, Christianne Shellie A. (School of Economics, University of the Philippines Diliman, 2018)
Payment may be considered a primary and the most used financial service in multiple countries including the Philippines. Such importance led to the need to develop the payments system through technology and innovations, thus the emergence of electronic payments. This study focuses on the locational characteristics of the city_municipality the respondent lives in, as well as individual_level characteristics. It examines its effects on the likelihood of an individual to use electronic payments. There is a total of 1,175 observations for the study using a cross_sectional data set from the 2016 E_Peso Individual Payments Baseline Survey conducted by the United States Agency for International Development (USAID), together with the Department of Trade and Industry_s 2016 Cities and Municipalities Competitive Index (CMCI), and the Philippine Statistic Authority_s 2012 City and Municipal Level Poverty Estimates. The study implements a logistical regression model in order to assess the relationships between the variables. Results show that the sum of the Economic Dynamism and Government Efficiency scores of the city_municipality is not statistically significant in influencing an individual to use e_payments, whereas the Infrastructure score proves to be significant. Belonging in the Second and Fourth or Fifth City Income Class levels are also statistically significant relative to residing in a First City Income Class. Individuals who also completed collegiate education, have an internet connection, are female, and are working also prove to be significant factors for an individual to adopt electronic payment systems. The findings of the study confirmed that there is a need to address and target education, access to the internet, and improving employment opportunities to increase the likelihood of the adoption of electronic payments. It also suggests the provision of infrastructures to aid in the increase of exchange of goods and services. This would lead to the increased efficiency and sustainability of economic activities in a particular location. These would encourage the adoption of electronic payments in the Philippines.